Contribution of NK cells to immunotherapy mediated by PD-1/PD-L1 blockade - Joy Hsu; Jonathan J. Hodgins; Malvika Marathe; Chris J. Nicolai; Marie-Claude Bourgeois-Daigneault; Troy N. Trevino; Camillia S. Azimi; Amit K. Scheer; Haley E. Randolph; Thornton W. Thompson; Lily Zhang; Alexandre Iannello; et al. (The Journal of Clinical Investigation, 2018)
Checkpoint blockade immunotherapy targeting the PD-1/PD-L1 inhibitory axis has produced remarkable results in the treatment of several types of cancer. Whereas cytotoxic T cells are known to provide important antitumor effects during checkpoint blockade, certain cancers with low MHC expression are responsive to therapy, suggesting that other immune cell types may also play a role. Here, we employed several mouse models of cancer to investigate the effect of PD-1/PD-L1 blockade on NK cells, a population of cytotoxic innate lymphocytes that also mediate antitumor immunity. We discovered that PD-1 and PD-L1 blockade elicited a strong NK cell response that was indispensable for the full therapeutic effect of immunotherapy. PD-1 was expressed on NK cells within transplantable, spontaneous, and genetically induced mouse tumor models, and PD-L1 expression in cancer cells resulted in reduced NK cell responses and generation of more aggressive tumors in vivo. PD-1 expression was more abundant on NK cells with an activated and more responsive phenotype and did not mark NK cells with an exhausted phenotype. These results demonstrate the importance of the PD-1/PD-L1 axis in inhibiting NK cell responses in vivo and reveal that NK cells, in addition to T cells, mediate the effect of PD-1/PD-L1 blockade immunotherapy.